1998
DOI: 10.1152/ajpcell.1998.275.5.c1365
|View full text |Cite
|
Sign up to set email alerts
|

Biotin uptake by human colonic epithelial NCM460 cells: a carrier-mediated process shared with pantothenic acid

Abstract: Previous studies showed that the normal microflora of the large intestine synthesizes biotin and that the colon is capable of absorbing intraluminally introduced free biotin. Nothing, however, is known about the mechanism of biotin absorption in the large intestine and its regulation. To address these issues, we used the human-derived, nontransformed colonic epithelial cell line NCM460. The initial rate of biotin uptake was found to be 1) temperature and energy dependent, 2) Na+ dependent (coupling ratio of 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 42 publications
5
80
0
Order By: Relevance
“…Biotin uptake was performed in lymphocytes from the proband and normal controls as previously reported (Said et al 1998) using Krebs-Ringer (KR) buffer (in mM: 133 NaCl, 4.93 KCl, 1.23 MgSO 4 , 0.85 CaCl 2 , 5 glucose, 5 glutamine, 10 HEPES and 10 MES, pH 7.4). Briefly, lymphocytes were harvested by centrifugation and equal amount of cells were used for uptake studies for 5 min as described previously.…”
Section: Biotin Uptake Studiesmentioning
confidence: 99%
“…Biotin uptake was performed in lymphocytes from the proband and normal controls as previously reported (Said et al 1998) using Krebs-Ringer (KR) buffer (in mM: 133 NaCl, 4.93 KCl, 1.23 MgSO 4 , 0.85 CaCl 2 , 5 glucose, 5 glutamine, 10 HEPES and 10 MES, pH 7.4). Briefly, lymphocytes were harvested by centrifugation and equal amount of cells were used for uptake studies for 5 min as described previously.…”
Section: Biotin Uptake Studiesmentioning
confidence: 99%
“…Colonic absorption of biotin has been demonstrated in humans and pigs (Sorrell et al, 1971;Barth et al, 1986). This uptake appears to be SMVTmediated, based on demonstration of an Na ϩ -dependent, specialized carrier-mediated system for biotin uptake in a human-derived, nontransformed colonic epithelial cell line (Said et al, 1998). Furthermore, our own studies have shown a significant level of mRNA encoding SMVT in fresh human colonic tissue biopsy samples, based on quantitative PCR (K. Woodford and N. Zerangue, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The prodrug also demonstrated a 5-fold apical to basolateral preference for permeation across cultured intestinal cell monolayers. SMVT and MCT-1 are broadly expressed along the intestinal tract of rats and humans (Said et al, 1998;Juel and Halestrap, 1999;Wang et al, 1999;K. Woodford and N. Zerangue, unpublished data).…”
mentioning
confidence: 99%